(untitled) (Web of Teachers: Inderscience Research, 2024)
This article provides information about the work of the German writer Fritz Wurtle, The Prince of Andijan. In this, Zahiriddin Muhammad Babur’s life path and the difficulties he experienced during his life are presented. This article describes the life path of Andijan prince Zahiriddin Muhammad Babur.